The Formulation and Stability Test of The Balm Emprit Ginger (Zingiber officinale var. amarum) Essential Oil - Ferna Indrayani; Nurul Hikma (Indonesian Journal of Pharmaceutical Education, 2022)
Emprit ginger (Zingiber officinale var. amarum) is a rhizome plant that is much of the time tracked down in the locale. Tanasitolo, Kab. Wajo. Its utilization is most generally utilized as a cooking zest, defeating joint inflammation, muscle torment, treating colds, treating hacks, as a characteristic cell reinforcement and warming the body. The compound parts contained in emprit ginger (Zingiber officinale var. amarum) are zingiberene, shagaol, sap, and gingerol which are adequate as cancer prevention agents and mitigating or then again reflexology. This study aims to decided how to of ginger emprit (Zingiber officinale var. amarum) as a salve form of a natural balm. This type of research is a direct observation in the laboratory using the distillation method to obtain the essential oil in ginger emprit (Zingiber officinale var. amarum) was then made in the form of a balm with different concentrations of essential oils, namely F1 (0 g), F2 (1.5 g), and F3 (2 g) using accelerated stability testing on the balm preparation, stored for 6 days with 3 cycles (40C and 400C) the observations included organoleptic tests (shape, smell, and colour), homogeneity test, pH test, spreadability test, adhesion test, and specific gravity.. This study indicate that a stable balm preparation that meets the standard requirements based on SNI with accelerated stability testing is formula F3 with a concentration of 2 grams of ginger essential oil. Emprit ginger (Zingiber officinale var. amarum) can be formed in a balm preparation.